Program Pemberdayaan Dhuafa Keluarga Bapak Zaidan Habibi Melalui Bantuan Modal Usaha Es Kobok - Zaviier, Abdurrahman; Al Muzaki, Marsan; Kurniawan, Rizqy; Habibi , Mulkan (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
Muhammadiyah is an Islamic organization with an Islamic movement that adheres strictly to the Al-Qur'an and Hadith. KH. Ahmad Dahlan as the founder of Muhammadiyah taught that one of the main foundations of the Muhammadiyah movement is the theology of Surah Al-Ma'un, which is based on three pillars, namely: health, education and social services. Worship has no meaning if Muslims ignore the suffering of others. Therefore, Al-Ma'un's theology teaches the importance of caring for others through social action and charity. Social charity movement through sources of economic empowerment for the poor through providing basic goods. Business aimed at improving Zaidan Habibi's economic welfare. Based on the results of Zaidan Habibi's economic empowerment activities, it shows that there is economic development from Zaidan Habibi because of the basic assistance given to him.